Psychopathy and chronotype disposition: the mediating role of depression. Issue 11 (November 2019) - Akram, Umair; Stevenson, Jodie C.; Gardani, Maria; Akram, Asha; Allen, Sarah
Abstract: This study examined the relationship between dark triad personality traits and chronotype disposition, whilst incorporating the mediating role of anxiety and/or depression after excluding individuals presenting insomnia and/or physiological sleep-disorder symptoms. Members of the general population (N = 453) completed online measures of dark triad personality traits, chronotype, and anxious and depressive symptoms. Psychopathy and Machiavellianism were independently related to an evening chronotype disposition. However, after accounting for age, sex, anxiety and depression, psychopathy and depression remained the only significant predictors of chronotype. Therefore, whilst psychopathy was the strongest predictor of an evening chronotype preference, this relationship is partially mediated by depression. Individuals presenting an evening disposition may display increased psychopathic traits due to greater emotion dysregulation. This is potentially perpetuated by depressive symptoms stemming from a delayed or blunted affective rhythm. Interacting factors (e.g. reduced light exposure) may also contribute to alterations in the biological rhythm amongst evening-types, resulting in a negative feedback cycle. Targeting chronotype and depressive symptoms amongst individuals presenting psychopathic tendencies could increase the efficacy of existing sleep-based interventions for hostile behaviour. Abstract : Neuroscience; Psychology; Circadian rhythm; Depression; Mental health; Psychological disorders; Personality; Dark triads; Depression; Chronotype; Diurnal preference; Psychopathy; Sleep.